Redefining the Term “Dialysis” in Efforts to Educate the Public and Eliminate Stigma Against Patients with Chronic Kidney Disease - Humairah Nur Sya’bani; Magrifatul Nasyila Tyandra; Rahma Febianti; Kanaya Azzahra; Muhammad Arief Rekozar (Indonesian Journal of Multidisciplinary Science, 2026)
Chronic Kidney Disease (CKD) has become a global health crisis with an increasing prevalence in Indonesia. Although hemodialysis is a crucial medical procedure to sustain life, the popular use of the term "dialysis" in society actually triggers negative perceptions and psychological barriers for patients. This conceptual article aims to analyze the impact of the use of the term through the perspective of Erving Goffman's Stigma theory and psycholinguistic principles in medical communication. The results of the study showed that the diction of "dialysis" creates a scary stigma and has the potential to reduce the level of medication adherence. Through a comparison with the successful transformation of other medical terms in Indonesia, such as ODGJ and STI, this article offers a redefinition of the term through three alternatives, namely renal function replacement therapy, blood screening therapy, or consistent use of the term direct hemodialysis. The conclusion of this study confirms that adjusting medical terminology to be more humane and accurate is an important step to reduce social stigma and build mental preparedness of patients. By implication, healthcare workers are advised to integrate psycholinguistic aspects in therapeutic communication to create a more empowering medical narrative.